2012
DOI: 10.1111/j.1600-0609.2012.01788.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in elderly, newly diagnosed multiple myeloma patients treated with VMP vs. MP: results from the VISTA trial

Abstract: These findings demonstrate clinically meaningful, transitory HRQoL decrements with VMP and relatively lower HRQoL vs. MP during early treatment cycles, associated with the expected additional toxicities. However, HRQoL is not compromised in the long term, recovering by the end-of-treatment visit to be comparable vs. MP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 53 publications
4
53
1
1
Order By: Relevance
“…The HRQoL decrease upon PD captured quantitatively here is also consistent with qualitative results on the burden of relapse on MM patients' emotional and physical well-being. 48 This adds additional support to the validity of the HRQoL measures included in the FIRST trial; further evidence of their reliability was also seen in the similarity in base-line scores between the FIRST, VISTA, 45 and HOVON 49 49 studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The HRQoL decrease upon PD captured quantitatively here is also consistent with qualitative results on the burden of relapse on MM patients' emotional and physical well-being. 48 This adds additional support to the validity of the HRQoL measures included in the FIRST trial; further evidence of their reliability was also seen in the similarity in base-line scores between the FIRST, VISTA, 45 and HOVON 49 49 studies.…”
Section: Discussionmentioning
confidence: 89%
“…44 However, our results contrast with the HRQoL trade-off reported with bortezomib in the VISTA trial, which compared MPV versus MP in NDMM patients and in which MPV had superior PFS and OS efficacy, but where patients' HRQoL was significantly compromised, especially in the first four cycles of treatment. 45,46 In the FIRST trial, although HRQoL was improved and maintained during the progression-free state, it deteriorated when disease progression occurred, regardless of the treatment received. This finding augments the clinical importance/benefit of the prolonged PFS, and time to progression observed with Rd versus MPT, 19 as a longer PFS in this comparison is associated with better HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…These findings differ from those of the VISTA trial, which evaluated the addition of bortezomib to MP (VMP) in transplant-ineligible patients with NDMM. 24 Since in the VISTA trial, HRQoL scores worsened during the first 4 cycles of VMP therapy compared with baseline and with MP, further studies are needed directly to compare the HRQoL impact of novel anti-myeloma treatment regimens.…”
Section: Mpr-r Hrqol Impactmentioning
confidence: 99%
“…VISTA included prospective evaluation of health-related quality of life (HRQoL) as measured by the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire (QLQ-C30). Review of these data showed a decrease in quality of life associated with initiation of PCM treatment with both VMP and MP, followed by recovery of HRQoL in both groups by completion of treatment [88].…”
Section: Melphalan Prednisone and Bortezomibmentioning
confidence: 99%